Archivi del futuro: la fantascienza letteraria tra Afrofuturismo e Africanfuturismo (Comparatismi, 2025)
Drawing on the concept of “double estrangement”, theorized by Joy Sanchez-Tayor to highlight the specificities of speculative fiction by writers of color, this article examines Afrodiasporic and African science fiction through a comparative analysis of the two subgenres of Afrofuturism and Africanfuturism. The aim is twofold: first, to demonstrate how these literary expressions rework the conventional tropes of science fiction through decolonial, feminist, and post-anthropocentric perspectives; second, to identity the conceptual and thematic specificities that set the two subgenres apart. Finally, the article turns to a comparative analysis of two case studies: The Deep (2019) by Rivers Solomon and the Binti trilogy (2015-2018) by Nnedi Okorafor, taken respectively as emblematic examples of Afrofuturist and Africanfuturist literature.
Keywords: Science fiction; Afrofuturism; Africanfuturism; Rivers Solomon; Nnedi Okorafor